FAKTOR-FAKTOR PERMINTAAN DAN NILAI EKONOMI AGROWISATA SWEETBERRY DENGAN PENDEKATAN TRAVEL COST METHOD - Anggiana Ruspandi, Dera; Kamilah, Ahya (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2023)
Sweetberry agrotourism is the largest strawberry farming in Puncak, Cipanas Cianjur, West Java. This agrotourism has the potential of nature, tourism, conservation, and economic potential. The purpose of this research is to identify the characteristics and assessment of visitors, identify factors influencing tourism demand, and estimate the value of agrotourism economy. The economic value is analyzed using by method of TCM (Travel Cost Method). This method is calculated based on total consumer surplus, travel cost coefficient, and total respondent's visit. Average travel costs incurred from a total of 379 respondents during the trip is Rp. 413.699 and the total cost of the entire trip is Rp.156.792.000. Surplus of consumer visits is Rp. 12.670 and the individual consumer surplus visits is Rp.33. The economic value generated for one year is Rp. 237.600. The factors that influence the demand is income, distance and time to know location. While the factors that do not affect the demand is travel cost, education, number of dependents in the family, gender, and age of visitor.